2019
DOI: 10.1175/jas-d-19-0139.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Fluxes Modulate the Seasonality of Zonal-Mean Storm Tracks

Abstract: The observed zonal-mean extratropical storm tracks exhibit distinct hemispheric seasonality. Previously, the moist static energy (MSE) framework was used diagnostically to show that shortwave absorption (insolation) dominates seasonality but surface heat fluxes damp seasonality in the Southern Hemisphere (SH) and amplify it in the Northern Hemisphere (NH). Here we establish the causal role of surface fluxes (ocean energy storage) by varying the mixed layer depth d in zonally symmetric 1) slab-ocean aquaplanet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The second configuration is a slab ocean aquaplanet general circulation model with modern obliquity, greenhouse gases, zero ocean energy transport, and thermodynamic sea ice (a motionless single slab, Giorgetta et al, 2012), hereafter referred to as AQUA. The modern AQUA simulation has a 50‐m mixed layer depth (Barpanda & Shaw, 2020; Donohoe et al, 2014). Here we vary the mixed layer depth as a simple way of simulating a range of climates between modern and Snowball Earth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second configuration is a slab ocean aquaplanet general circulation model with modern obliquity, greenhouse gases, zero ocean energy transport, and thermodynamic sea ice (a motionless single slab, Giorgetta et al, 2012), hereafter referred to as AQUA. The modern AQUA simulation has a 50‐m mixed layer depth (Barpanda & Shaw, 2020; Donohoe et al, 2014). Here we vary the mixed layer depth as a simple way of simulating a range of climates between modern and Snowball Earth.…”
Section: Methodsmentioning
confidence: 99%
“…The storm track interacts with the terms on the right hand side of (5); thus, it is difficult to infer causality when the MSE framework is used diagnostically. However, Shaw et al (2018) and Barpanda and Shaw (2020) showed that external parameters in the MSE framework (e.g., insolation and mixed layer depth) can form the basis of predictions, scaling estimates, and thereby causal understanding.…”
Section: Mse Frameworkmentioning
confidence: 99%
“…Poleward heat transport (PHT) works toward energy balance by moving heat from warmer to colder regions (e.g., Held, 2001; Trenberth & Stepaniak, 2003), primarily via atmospheric but also via oceanic pathways (Czaja & Marshall, 2006; Held, 2001). Atmospheric warming from anthropogenic climate change is also spatially varying, for example, in tropical upper‐ and Arctic lower‐tropospheric warming (e.g., Deser et al., 2016; Vallis et al., 2015), which entails changes to PHT that also occur via the atmospheric pathway (e.g., Alexeev & Jackson, 2013; Barpanda & Shaw, 2020; Hwang & Frierson, 2010; Hwang et al., 2011; Shaw et al., 2018). Changes in PHT in observations have also been linked to reduced reflected shortwave radiation due to sea ice loss to reduced high‐latitude PHT (Hartmann & Ceppi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The MSE budget has the appeal of interpreting the tropical and extratropical atmospheric circulations (including baroclinic eddies) as part of the global energy budget and relating them to sources and sinks of energy through the top and the bottom of the atmospheric column, as well as atmospheric and surface energy storage. By applying this framework to the understanding of the seasonality of zonal-mean storm tracks in aquaplanet simulations at Earth's obliquity, Barpanda and Shaw (2020) for instance showed how a large heat capacity of the lower boundary buffers insolation through surface fluxes, resulting in small seasonality of the net energy input and, with it, of the storm tracks, as for instance seen in Earth's Southern Hemisphere. For small mixed layer depths, they found a large seasonality of the net energy input, which leads to a large storm track seasonality, but also an increasing role for atmospheric energy storage.…”
Section: Accepted Articlementioning
confidence: 99%